Cultural influences on normative reactions to incivility: comparing individuals from South Korea and Spain. Issue 2 (10th September 2020) - Moon, Chanki; Sánchez‐Rodríguez, Ángel
Abstract : Purpose: Antecedents and influences of workplace incivility have recently been studied in many areas of research but there is still a lack of consideration for the impact of culture. Theoretical considerations for the present research are based on the cultural dimensions of power distance and tightness/looseness because the collective levels of power distance are similar between Korea and Spain, but the collective levels of tightness/looseness are different between the two countries. The purpose of this paper is to examine whether individuals' occupational position affects their normative reactions to incivility differently. Design/methodology/approach: Participant (victim)'s (those who react to uncivil behaviors) social power (low vs high) and perpetrator's (those who exhibit uncivil behaviors) social power (low vs high) were experimentally manipulated; all participants were randomly assigned to one of four perpetrator × victim conditions in relation to hierarchical positions ( Ntot = 467). Findings: The results suggest that the level of social and personal acceptability was greater either among Koreans than Spanish at a collective level or among people who endorsed higher power distance and tightness values. All in all, the findings highlight cultural influences on the importance of social hierarchy as a factor that can impact the people's normative reactions to incivility. Originality/value: The findings broaden our understanding of the psychology of employees in relation to incivility, by simultaneously considering the influences of culture (power distance and tightness/looseness) and social power.